2014
DOI: 10.1371/journal.pone.0115223
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Selection of Resistant E. coli after Ingestion of Milk with Added Drug Residues

Abstract: Antimicrobial resistance represents a major global threat to modern medicine. In vitro studies have shown that very low concentrations of drugs, as frequently identified in the environment, and in foods and water for human and animal consumption, can select for resistant bacteria. However, limited information is currently available on the in vivo impact of ingested drug residues. The objective of our study was to evaluate the effect of feeding preweaned calves milk containing antimicrobial drug residues (below… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
75
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(86 citation statements)
references
References 71 publications
6
75
2
3
Order By: Relevance
“…Likewise, on the individual calf level, feeding WM regardless of the type of antimicrobial treatment the cow was given led to an increased proportion of QREC in the calf feces. Likewise, WM feeding has been shown by others to increase the shedding of resistant E. coli in feces of calves (Wray et al, 1990;Aust et al, 2013;Brunton et al, 2014;Pereira et al, 2014b;Rebelo, 2014) and when the concentration of antimicrobials in WM is low (Pereira et al, 2014b). The use of fluoroquinolones during the previous 4 mo was low (only 1.2 cases per 100 cow-years) and hence, few of the calves in the current study could have been fed WM from fluoroquinolone-treated cows.…”
Section: Discussionmentioning
confidence: 55%
“…Likewise, on the individual calf level, feeding WM regardless of the type of antimicrobial treatment the cow was given led to an increased proportion of QREC in the calf feces. Likewise, WM feeding has been shown by others to increase the shedding of resistant E. coli in feces of calves (Wray et al, 1990;Aust et al, 2013;Brunton et al, 2014;Pereira et al, 2014b;Rebelo, 2014) and when the concentration of antimicrobials in WM is low (Pereira et al, 2014b). The use of fluoroquinolones during the previous 4 mo was low (only 1.2 cases per 100 cow-years) and hence, few of the calves in the current study could have been fed WM from fluoroquinolone-treated cows.…”
Section: Discussionmentioning
confidence: 55%
“…Some studies have investigated changes in antimicrobial resistance in the intestinal bacteria of preweaned calves being fed milk (Langford et al, 2003;Pereira et al, 2014b) or milk replacer (Thames et al, 2012) when increasing levels of antimicrobials were experimentally added to the milk diet. Langford et al (2003) and Pereira et al (2014b) both reported increased phenotypic resistance in intestinal bacteria for calves on medicated milk diets, whereas Thames et al (2012) did not observe an effect of diet on genes encoding for antimicrobial resistance in calf feces. However, limitations of these studies included the use of a relatively small number of calves under conditions of artificial exposure to antimicrobials.…”
Section: Introductionmentioning
confidence: 99%
“…However, limitations of these studies included the use of a relatively small number of calves under conditions of artificial exposure to antimicrobials. Furthermore, Langford et al (2003) and Pereira et al (2014b) only sampled calves for a short period (≤6 wk of age) while on the milk diet. Conversely, Thames et al (2012) sampled calves both pre-and postweaning (wk 6, 7, and 12).…”
Section: Introductionmentioning
confidence: 99%
“…Calves could have acquired drug resistant bacteria and resistant genes from their mothers during birth, from the waste milk used as feed [26,27] or from the environment [8,28], including cross-contamination through farm workers and feeding equipment [29]. Studies have found AMR genes in animals raised without antimicrobials as well [30,31].…”
Section: Discussionmentioning
confidence: 99%